Analysis of the morphological variability of the bream (Abramis brama Linnaeus, 1758) Dnipro-Buh river mouth system - Gеіna, Konstantin (ScienceRise: Biological Science, 2018)
Hydraulic construction on the Dnipro River led to dramatic changes in the ichthyocenosis of the estuarine waters. As a result of the regulation of the natural flow, the dynamic balance between the abiotic and biotic parameters of the habitat of aquatic organisms throughout the Dnipro-Buh river mouth system was disturbed. Transformational processes that have lasted to the present time are accompanied by changes in the main structural characteristics of ichthyocenosis, where one of the most valuable representatives of commercial cyprinids has always been the bream – Abramis brama Linnaeus, 1758. Purpose. To conduct a morphometric analysis of bream of the Dnipro-Buh river mouth system in modern conditions. To compare the results with scientific data for previous periods of succession of the ecosystem of the Dnipro-Buh river mouth system. To explain the causes of morphological variability of bream over time and analyze sexual dimorphism in the herd. Materials and methods. The research work is carried out in accordance with generally accepted methods of ichthyological research. Morphological variability is determined by Student's t-test (td). Bream individuals from age groups of five-year-old and six-year-olds are used for analysis, which makes it possible to compare the obtained data with the results of previous studies. Results. The study of the meristic signs of bream shows that at present the formulas of the fins are as follows: D - III 9 (10); A - III 24-26 (27); P - I 16-18; V - II 7-8; C I 19 I, and in the sideline there are from 53 to 56 scales. The results are within the limits of similar scientific data of the last century. It is established that the most significant changes in the proportions of the body in bream during the transformation of the drain of the Dnipro occur in height and length of the dorsal fin (td=7.5-8.7; р<0,05). At the same time, an elongation of the caudal stem (td=10.2; p<0.05) and a decrease in the ante-anal distance (td=4.0; p<0.05) are noted. The presence of sexual dimorphism in the herd is proved. Among the 22 analyzed plastic signs, a significant difference is found for 13 indicators. In males, due to greater mobility, the anal fin is located closer to the fish snout (td=3.38; p<0.05), the head is more pointed (td=3.77; p<0.05) and below the body (td=3.5; p<0.05). Conclusions. A comparative analysis of modern plastic signs of bream in the Dnipro-Buh river mouth system indicates changes in the proportions of the body. At present, it has been reliably established that the anal fin has shifted closer to the anterior end of the body (td=4.0; p<0.05), which is a consequence of the fundamental redistribution of river flow and a decrease in the flow velocity. This is the situation that led to the lengthening of the migration routes of the bream in the Dnipro-Buh river mouth system and the formation of a population that is characterized by high mobility.